Msit No'kmaq: an exploration of positionality and identity in Indigenous research - Jackson, Margot; Hurley, Erica (My University, 2020)
In this paper I explore the Mi’kmaq words Mist No’kmaq, which can be translated as ‘all my relations’. Msit No'kmaq is not only at the center of who I am as a person, but also who I am becoming as a researcher. Reflecting on how to honor all my relations within research, has allowed me to explore my beliefs about research, thereby developing a clear understanding of the purpose and intentions of engaging in Indigenous research. Rather than seeing researchers as insiders or outsiders within the context of Indigenous communities, I argue that it is important to engage in reflexive processes that make visible a researcher’s positionality and who they are and are becoming.
Keywords: identity; positionality; Indigenous research; relations; relational accountability